Occipital Neuralgia May Be a Possible Limitation on the Utility of the Buffalo Treadmill Test for Concussion Assessments: 2 Case Reports. Issue 5 (11th September 2022) - Cook, Laura; Herman, Daniel C.
Abstract: Two female athletes presented to clinic following a head injury and exhibited signs of concussion. Both athletes experienced exacerbation of symptoms secondary to dysautonomia related to concussion injury on the Buffalo Concussion Treadmill Test (BCTT). On repeat evaluation, both athletes exhibited neck pain with symptoms immediately provoked by palpation of the occipital nerves. After a third occipital nerve block, both athletes had complete resolution of symptoms and subsequently tolerated BCTT to the maximum rate of perceived exertion with no provoked symptoms. The athletes were cleared for return to sport without issue. These cases indicate a potential limitation in the utility of the BCTT for determining the etiology and management of concussion and postconcussion syndrome.